TECHNOLOGY AND INTERPERSONAL SKILLS IN MEDICAL SECRETARIAL PRACTICE: A COMPARATIVE ANALYSIS - Sitah Jehad Ali Alharbi, Khadijah Mohammed Abdu Asiri, Bashayr Mohammed Hassan Majrasha, Aljazi N N Alharabi, Nuwayyir Awadh Farhan Alshammari, Nouf Garby Al enazy (Chelonian Research Foundation, 2022)
The role of medical secretaries in healthcare organizations has evolved with the increasing adoption of technology, such as electronic health records (EHRs). This study aimed to compare the importance of technological skills and interpersonal skills in medical secretarial practice in Saudi Arabian hospitals. A cross-sectional survey was conducted among 312 medical secretaries from six hospitals in Riyadh, Saudi Arabia. The survey included questions on demographic characteristics, perceived importance of technological and interpersonal skills, job satisfaction, and self-reported job performance. Data were analyzed using descriptive statistics, paired samples t-tests, and multiple linear regression. The results showed that medical secretaries perceived both technological and interpersonal skills as highly important for their job, with interpersonal skills being rated slightly higher than technological skills. job satisfaction and self-reported job performance were positively associated with both skill sets, but interpersonal skills had a stronger predictive power. The findings suggest that while technological skills are essential for medical secretaries in the era of EHRs, interpersonal skills remain crucial for effective job performance and satisfaction. Healthcare organizations should provide training and support for both skill sets to enable medical secretaries to thrive in their roles. Keywords: medical secretaries, technological skills, interpersonal skills, electronic health records, job satisfaction, job performance